Wyobrażenia o sobie i swojej przyszłości w aspekcie stosunku do ojczyzny = The idea of yourself and your future in relation to the native land - Byzova, Valentina M.; Perikova, Ekaterina I. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article contains empirical results of a study of the sample of Finno-Ugric youth of the Komi Republic, living in St. Petersburg. The results of self-perception, self-image and attitude to the future are considered depending on the attitude towards the Native land: negative, ambivalent or positive.
Keywords: postawa wobec ojczyzny; obraz siebie; tożsamość; attitude towards the Native land; self-image; identity